Climate Risk & Vulnerability (CR&V) assessment for climate services: Fruit production and value chain - Mekong River Delta, Viet Nam - Le, Thi Tam; Pham, Thi Kim Dung; Tuan, Manh Lam; Giles, James; Swaans, Cornelis (2023)
As part of the CGIAR Initiative on Asian Mega-Deltas, a scoping study was completed by the end of 2022 to prioritize key delta-oriented production systems and value chains in Viet Nam's Mekong River Delta (MRD) (Gonsalves et al., 2022). Rice, rice-shrimp, and fruit trees production systems and value chains were selected based on a set of criteria including production, economic and nutritional value, climate change and impact, and potential benefit of climate services with specific attention for the role of women and smallholders. To better understand the selected commodity production systems in the MRD, an additional value chain climate risk and vulnerability assessment was made. This report focuses on fruit production and its value chain. In consultation with the Department of Crop Production and provincial partners in the MRD, we particularly focus on mango, durian, and citrus fruits. These are important fruits in the MRD with large cultivated areas, high productivity, and high potential export value. However, they are also sensitive to climate variability during production, harvesting, and selling stages and may benefit from climate information services.